Content Test of Escherichia and Salmonella sp. Bacteria on Fish Sago in Dehigila Village, Morotai Island Regency - Asy’ari Asy’ari; Titien Sofiati; Iswandi Wahab; Jana Sidin (Faculty of Agriculture Musamus University, 2020)
Fish is one of the foodstuffs that has a protein content that is needed by humans. Nowadays fish have been processed into many products that have longer durability, humans have used fish as a mixture in diversified products. Diversification of fishery products so that fish can be used in other forms such as instant noodles, biscuits, and traditional products such as making sago plates mixed with fish meat. The purpose of this study was to determine the content of E. coli and Salmonella sp. on sago products produced. This research was conducted in September-October 2019. Sampling of fish sago was carried out in Dehegila Village, Morotai Island Regency. Sample analysis was performed at the Khairun University Ternate Environmental Laboratory. The data obtained were then presented in a descriptive analytic and literature study. From the results of the study obtained by sago plate added skipjack tuna meat as well as the use of flavorings Based on the analysis of all sago samples there was bacterial growth with an average number <0.30. While for Salmonella sp. on sago Ao and A1 negative / 25 g.